DESKRIPSI KOMPETENSI DAN MOTIVASI PEGAWAI TERHADAP KINERJA DI BALAI DIKLAT KEAGAMAAN BANDUNG - Ranti Nuranita (JENTRE, 2021)
Competence, motivation and performance are an important part of a government institution that plays a role in achieving the vision of the government institution. This attracts researchers to conduct research with the aim to determine the effect of competence and motivation both simultaneously and partially on employee performance. The research method used a survey method with 78 respondents. The research data includes primary data taken through a Likert scale questionnaire, where the level of validity and reliability has been tested first. The analytical method used is descriptive and verivative with technical path analysis. The test results showed that competence and motivation together had an effect of 26% on employee performance and the remaining 74% came from other factors not examined by the researcher. Partially the influence of motivation on employee performance is more dominant than competence